Self-perception of stuttering: association with self-perception of hearing, fluency profile, and contextual aspects - Camila Eduarda Elias Silva; Denise Brandão de Oliveira Britto; Stela Maris Aguiar Lemos (CoDAS)
ABSTRACT Purpose This study investigated the association between self-perception of stuttering and self-perception of hearing, speech fluency profile, and contextual aspects in Brazilian adults who stutter. Methods Fifty-five adults who stutter (ages 18 to 58 years), speakers of Brazilian Portuguese speakers, participated in an observational study that included: (a) a clinical history survey to collect identification, sociodemographic, clinical, and assistance data; (b) the Brazil Economic Classification Criteria (CCEB); (c) a hearing self-perception questionnaire (Speech, Spatial and Qualities of Hearing Scale – SSQ, version 5.6); (d) self-perception of the impact of stuttering (Brazilian Portuguese version of the Overall Assessment of the Speaker's Experience of Stuttering – Adults – OASES-A); and (e) an assessment of speech fluency (Fluency Profile Assessment Protocol -- PAPF). Data analysis consisted of descriptive and bivariate analysis using Pearson’s chi-square, Mann-Whitney, Kruskal-Wallis, and Spearman correlation coefficient. Results Most participants were classified as moderate to severe in the total classification of the impact of stuttering. There were moderate and weak negative correlations between the participants' self-perception of stuttering and self-perception of hearing. Conclusion Self-perception of auditory abilities was greater to the extent that self-perception of the impacts of stuttering on quality of life was lower.